IMPLEMENTASI KEBIJAKAN PEMBELAJARAN DARING PADA MASA PANDEMI COVID-19 DI KOTA LHOKSEUMAWE - Risna Dewi; Muhammad Israq Ayuda (Sekolah Tinggi Ilmu Administrasi Nasional, 2022)
This study explores the implementation of learning policies in Lhokseumawe city, Indonesia, during the COVID pandemic. The research was conducted to determine whether the schools utilized any form of online education during the Covid-19 pandemic. A qualitative method was applied in collecting the data through observation, interviews, and document analysis. Findings show that the implementation of online learning during the COVID-19 pandemic did not find a satisfactory and effective resolution, particularly at SMK Negeri 2 Lhokseumawe. According to students at this school, students needed more engagement and interactive activity while participating in the online teaching and learning process. Because the education office recreates such a significant role in the resolution of issues about online schools, SMK Negeri 2 Lhokseumawe only has a limited number of resources at the school besides qualified and trained teachers and teaching staff.